2021
DOI: 10.1093/mmy/myab048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of overtime phenotypic variation of yeasts in chronic vulvovaginal candidosis cases

Abstract: Chronic vulvovaginal candidosis results either from reinfection or from the ability of Candida spp. to persist in the vulva and/or vagina. Persistence is usually associated with increased antifungal (mainly azoles) resistance rates, which can explain treatment failure, and/or increased expression of virulence factors by Candida spp. The aim of this study was to assess the mechanisms leading to Candida spp persistence, by studying sequential isolates from women with chronic vulvovaginal candidosis, focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, other studies that analyzed yeast isolates from vaginal samples of both infection and asymptomatic cases also detected differences in the proportions of the species obtained, as can be seen in four of the studies presented in Table 3. Considering that in chronic cases of vulvovaginal candidosis investigators reported that, in approximately 53% of these cases, the episodes were due to genetically related isolates [26], we decided to count each species only once per patient per anatomical site in order to avoid characterizing the same isolate that could have survived between infections.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies that analyzed yeast isolates from vaginal samples of both infection and asymptomatic cases also detected differences in the proportions of the species obtained, as can be seen in four of the studies presented in Table 3. Considering that in chronic cases of vulvovaginal candidosis investigators reported that, in approximately 53% of these cases, the episodes were due to genetically related isolates [26], we decided to count each species only once per patient per anatomical site in order to avoid characterizing the same isolate that could have survived between infections.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest studies examined diversity by looking at 'resistogram' or phenotypic profiles of strains, by typing strains based on their ability to grow in a panel of diverse chemical challenges (45)(46)(47). This was followed by studies using many different methods of genomic profiling to assess relatedness among strains, such as rDNA restriction fragment length (48), DNA/PCR fingerprinting (40,(49)(50)(51), CHEF gel analysis (52), microsatellite loci (53)(54)(55)(56), and randomly amplified polymorphic DNA (RAPD) (51,(57)(58)(59). The highest genomic resolution and an ability to accurately map phylogenetic relationships among divergent strains come from recent studies that have used multilocus sequence typing (MLST) (18,60,61) and one very small study that employed whole genome sequencing (WGS) (62).…”
Section: Introductionmentioning
confidence: 99%